2016
DOI: 10.1111/jtsa.12224
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Modeling with a Generalized t Distribution

Abstract: Exponential generalized autoregressive conditional heteroscedasticity models in which the dynamics of the logarithm of scale are driven by the conditional score are known to exhibit attractive theoretical properties for the t distribution and general error distribution. A model based on the generalized t includes both as special cases. We derive the information matrix for the generalized t and show that, when parameterized with the inverse of the tail index, it remains positive definite in the limit as the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Further generalizations are possible. For example the generalized t ‐distribution may be used, as in the ARCH‐M model of Theodossiou and Savva (), and this may be extended to allow for different degrees of freedom in the upper and lower tails, as in Harvey and Lange (). Adding an ARCH‐M vector to a multivariate DCS volatility model of the kind proposed by Creal et al () is also possible, yielding a model which is much closer to the specification of Bekaert and Wu () than that of Bollerslev et al ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further generalizations are possible. For example the generalized t ‐distribution may be used, as in the ARCH‐M model of Theodossiou and Savva (), and this may be extended to allow for different degrees of freedom in the upper and lower tails, as in Harvey and Lange (). Adding an ARCH‐M vector to a multivariate DCS volatility model of the kind proposed by Creal et al () is also possible, yielding a model which is much closer to the specification of Bekaert and Wu () than that of Bollerslev et al ().…”
Section: Resultsmentioning
confidence: 99%
“…Following the discussion in Blasques et al (), a sufficient condition for invertibility can be found by generalizing the result in Harvey and Lange (, p. 182). The proposition below is for the Beta‐t‐EGARCH‐M model, to , but with the ARCH‐M score term dropped from .…”
Section: Model Formulationmentioning
confidence: 86%
“…The critical value is 3.64 for a single parameter restriction at a 5% level of significance. 13 The asymmetric skew generalized t model of Harvey and Lange (2017) was also estimated for all series and compared via LRTs. The tests failed to reject the simpler AST DCS model at a 10% level for the FTSE, NASDAQ, Kospi and Bovespa series, though improvements were found for the S&P 500 and DJIA.…”
Section: In-sample Estimation Resultsmentioning
confidence: 99%
“…For example, as = 2, it becomes Student-t with degrees of freedom. On the other hand, with →∞, the limiting case is GED( ), the generalized error distribution; see Harvey and Lange (2017) for a more detailed discussion. The distribution is quite flexible and therefore capable of capturing many empirically relevant situations, especially related with the occurrence of rare events.…”
Section: Methodsmentioning
confidence: 99%